Gamma variant of (p, q) -Bernstein type novel operators - Narendra Kurre (Journal of Hyperstructures, 2025)
In this paper, we are concerned with a new modification of the well-known (p;q)-Bernstein novel type operators with the gamma integral functions. The direct results demonstrate several aspects of approximations. Such as the rate of convergence theorem using Peetre's K-functional and Korovkin's theorem, which also validates the well-known Voronovskaja's theorem and the convergence theorem for Lipschitz continuous functions.